The Development of Casta Painting as Visual Genre in New Spain and the Production of Ethnoracial Stereotypes - Catelli, Laura (2024)
The aim of this essay is to analyze the ways in which the development of the casta pictorial genre contributed to the production and stabilization of racializing and racist stereotypes. These racial stereotypes still persist in cultural imaginaries in and about Latin America as part of the long duration of coloniality. Casta painting from New Spain is analyzed here as a pictorial genre and as a colonial discourse in connection with situated social and racial concepts, such as Creole, caste, and calidad. The analysis develops through a dialogue with perspectives from Semiology of Art, Visual studies, Postcolonial studies, and Latin American Critique of Coloniality. In this regard, this essay intends to create a conversation among different disciplines and fields of study in order to develop a complex, transdisciplinary approach to a problem from colonial times: the production and circulation of ethnoracial stereotypes and their impact on social relations, lived experiences, and subjectivities.